Identification of RNA instability elements in Borna disease virus - Siemetzki, Ulrike (Virus Res, 2009)
Genome organization and gene expression of Borna disease virus (BDV) are remarkable for the overlap of open reading frames, transcription units and transcription signals, read through of transcription termination signals, differential use of translation initiation codons, and exploitation of the cellular splicing machinery. Here we report an additional control of gene expression at the level of mRNA stability. Levels of BDV proteins in infected cells do not correspond to the transcriptional gradient typically observed in nonsegmented negative-sense RNA viruses. The third transcription unit of BDV’s negative-sense RNA genome encodes viral proteins M, G and L. Analysis of the third transcription unit identified RNA-destabilizing domains with the most pronounced activity located in regions spanning nucleotides 2818–2918 (instability domain-1) and 4022–4071 (instability domain-2). Given that one domain maps to intron-2 and is thereby eliminated upon splicing, this represents an intriguing mechanism for regulating transcript levels independent of a transcriptional gradient. The presence of instability domains in introns offers a mechanism to create the observed discontinuous gradient M>L>G, compatible with the non-cytopathic, persistent infection that is characteristic for BDV, and provides a rationale for the use of alternative splicing by this unusual virus.